An Unusual Cause of Sudden Bilateral Lower Extremity Weakness. (April 2022) - Steffens, Sarah; Yaffee, Anna Q.; Krakow, David; Patel, Dhruv
Abstract : Acute bilateral quadriceps tendon rupture is a musculoskeletal injury that requires urgent orthopedic surgical evaluation. Bilateral quadriceps tendon rupture is exceptionally rare, yet a missed diagnosis can result in long-term disability for the patient. This article presents a patient's case including the history, physical examination, key imaging findings, and management. This article emphasizes the importance of a detailed physical examination in patients presenting with musculoskeletal complaints as well as maintaining a broad differential diagnosis, which will assist the advanced practice provider in recognizing both the common and rare diagnoses in the emergency department.